2000
DOI: 10.1002/1099-0690(200006)2000:11<2079::aid-ejoc2079>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Study of 3,4‐Dihydro‐2(1 H )‐pyridones and Isoxazolo[5,4‐ b ]pyridin‐6(7 H )‐ones

Abstract: A series of isoxazolo [5,4-b]pyridin-6(7H)-ones (8) have been prepared with a high stereochemical control from the novel 3,4-dihydro-2(1H)-pyridones (7) by reaction with hydroxylamine hydrochloride and subsequent 5-endo-trig cyclization. A structural study by X-ray analyses and theoretical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…In previous works we have widely used theoretical calculations for determining the structural and conformational features of 1,4-DHPs and 3,4-dihydropyridone derivatives and we have demonstrated that ab initio and semiempirical calculations (at the AM1 level) reproduce adequately the geometry of this type of compound, taking into account the X-ray diffraction studies. [24][25][26][27] All compounds were calculated using a semiempirical AM1 method. In the case of model compounds 4k, 4n and 4o calculations were performed using ab initio HF/6-31G* and DFT (B3LYP/6-31G*) methods for the sake of comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works we have widely used theoretical calculations for determining the structural and conformational features of 1,4-DHPs and 3,4-dihydropyridone derivatives and we have demonstrated that ab initio and semiempirical calculations (at the AM1 level) reproduce adequately the geometry of this type of compound, taking into account the X-ray diffraction studies. [24][25][26][27] All compounds were calculated using a semiempirical AM1 method. In the case of model compounds 4k, 4n and 4o calculations were performed using ab initio HF/6-31G* and DFT (B3LYP/6-31G*) methods for the sake of comparison.…”
Section: Resultsmentioning
confidence: 99%
“…s, 9 Â CH 2 ), 0.85 (3H, t, J ¼ 6.4 Hz, CH 3 ); 13 C NMR (DMSO-d 6 ), d: 167.4 (C5-CQO), 166.9 (C3-CQO), 164.9 (C1 0 ), 149.1 (C3 0 ), 146.1, 146.0 (C2, C6); 135.5 (C5 0 ), 121.4, 121.2 (C4 0 , C6 0 ), 100.3 (C3) 100.2 (C5), 62.9 (OCH 2 ), 50.0 (OCH 3 ), 41.1 (C4), 31.3 (CH 2 ), 29.0 (2 Â CH 2 ), 28.9 (CH 2 ), 28.7 (CH 2 ), 28.6 (2 Â CH 2 ), 28.2 (OCH 2 CH 2 ), 25.5 (CH 2 ), 22.1 (CH 2 ), 18.3 (2 Â CH 3 ), 13.9 (CH 2 CH 3 ); MS-EI m/z(%) 456 (M 1 , 1), 378 (100), 271 (4), 210 (41), 178 (5) 3,5-dicarboxylate (4c). Obtained from 1g, 2a and 3a in 65% yield, mp: 167-169 1C, IR (KBr) n 3260 (NH), 2225 (CN), 1690 (CQO), 1628 and 1593 (CQC); 1 H NMR (DMSOd 6 ), d: 8.90 (1H, s, NH), 8.40 (1H, d, J ¼ 4.7 Hz, H3 0 ), 7.58 (1H, td, J ¼ 7.7 Hz, J ¼ 1.8 Hz, H5 0 ), 7.18 (1H, d, J ¼ 7.7 Hz, H6 0 ), 7.11 (1H, dd, J ¼ 7.7 Hz, J ¼ 4.7 Hz, H4 0 ), 5.01 (1H, s, H4), 4.14 (2H, t, J ¼ 6.0 Hz, OCH 2 ), 3.53 (3H, s, OCH 3 ), 2.83 (2H, m, CH 2 CN), 2.25 (3H, s, CH 3 -C2), 2.24 (3H, s, CH 3 -C6); 13 C NMR (DMSO-d 6 ), d: 167.4 (C5-CQO), 166.5 (C3-CQO), 164.7 (C1 0 ), 149.1 (C3 0 ), 147.2, 146.1 (C2, C6), 135.8 (C5 0 ), 121.6 (C6 0 ), 121.4 (C4 0 ), 118.8 (CN), 100.5 (C5), 99.5 (C3), 58.4 (OCH 2 ), 50.6 (OCH 3 ), 41.0 (C4), 18.6 (CH 3 -C2), 18.3 (CH 3 -C6), 17.5 (CH 2 -CN); MS-EI m/z(%) 341 (M 1 , 2), 263 (100), 210 (26), 178 (5). Anal.…”
Section: Synthesis Of 14-dihydropyridines (4)mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] Our literature survey revealed that there are some examples in the synthesis of 3,4-dihydro-α-pyranones by several groups. [24][25][26][27][28][29][30][31] But, little efforts have been paid to the synthesis of dihydropyranone and dihydropyrano [2,3-d] [1,3]dioxine-dione derivatives. [32][33][34][35][36][37][38] To make the synthesis of this kind of compound in a more efficient and in continuation of our studies on one-pot multi-component reactions, [39][40][41] we report here a one-pot three-component reaction of Meldrum's acid, arylaldehydes, and various 1,3-dicarbonyls in the presence of KOH as a base in H2O:EtOH under thermal and ultrasound irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In connection with our studies of novel calcium channel modulators, we have previously described the synthesis and conformational study of 5-alkoxycarbonyl-6-methyl-3,4-dihydropyridines 14 and 5-acetyl-4-aryl-3,4-dihydro-6-methyl-2(1H)-pyridones. 15 Recently we also reported a solid-phase synthesis method 16 and a solventfree synthesis under microwave irradiation of 5-alkoxycarbonyl-6-methyl-3,4-dihydropyridones. 17 We have also reported the mass spectrometric behaviour of substituted 3,4-dihydro-2(1H)-pyridin-2-ones by electrospray ionization and ion-trap fragmentation methods.…”
Section: Introductionmentioning
confidence: 99%